THE EFFORT TO IMPROVE STUDENT LEARNING ACTIVITIES IN PKN LESSONS THROUGH LEARNING METHOD LEARNING MATERIALS AND CONTEXTUAL INDONESIAN ROLE IN SOUTHEAST ASIA IN CLASS VI UPTD. NEGERI SD NO. 211 SABA DOLOK KOTANOPAN KABUPATEN MANDAILING NATAL ACADEMIC - Yuniar yuniar (JURNAL LINER (Language Intelligence and Educational Research), 2022)
This research was conducted at UPTD. State Elementary School No. 211 Saba Dolok, Kotanopan Subdistrict, Mandailing Natal Regency, this type of research is Classroom Action Research using the Contextual Teaching and Learning learning model in learning which aims to determine the extent to which the use of this method can improve student learning outcomes. The subjects this study were students of Class VI UPTD. State Elementary School No. 211 Saba Dolok, Kotanopan Subdistrict, Mandailing Natal Regency with a total of 25 students, 14 of whom are girls and 11 are boys. From the research carried out, it was found that there was an increase in learning outcomes after the action was carried out. There is an increase in student Civics learning outcomes through the application of the Contextual Teaching and Learning learning model to the material on the role of Indonesia in Southeast Asia. This can be seen from student learning outcomes in the first cycle, the percentage of student learning mastery is 71.4% and the score of class completeness is 62.5% with the lowest score of 50 and the best score of 70. In the second cycle, the percentage of student learning completeness is 100% and the score is class completeness score of 85.4% with the lowest score of 70 and the best score of 90. This value has met the indicators of success. This means that there is an increase in student Civics learning outcomes from cycle I to cycle II, for the percentage of student learning mastery there is an increase of 37.5% and the score of class completeness is 14.0%. The results of observing student activities in the first cycle were 61.75%, while in the second cycle it was 72.88%. This means that there is an increase in student activity from cycle I to cycle II by 11.13%. And the results of observations of teacher activities in the first cycle of 76%, while in the second cycle of 86%. This means that there is an increase in teacher performance from cycle I to cycle II by 10%. This means that the higher the activity of students in learning, the higher the value of learning outcomes obtained.